(untitled) (Semiárida, 2020)
The presence of helminths in the gastrointestinal tract, lung8 and liver of eighty 3 to 8 month old lambs were studied from September 1983 to October 1984. The goal was to determine the prevalence and abundance of regional parasite species. The samples were obtained from Sta Rosa slaughter (Frical S.A.). Sheep were brought from the departments of Capital, Toay, Atreucó, Guatraché, Catrlló, Utracán y Conhelo. The helminths recovered and their respective prevalence were as follow: Haemonchus contortus, 73.8%; Nematodirul spp, 64.6% (N. spathiger, N. oiratianus y N. abnormalis); Trichuris ovis, 58.4%; Trichostrongylus colubriformis, 46,1%; T. vitrinus, 20%; T. axei, 44.6%; 4.6%; C. curticei, 1.5%; -Oesopha Rostomum spp, 26.1 % lº’-.. vanulosum 66%, O. columbianum 34%); Chabartia ovina, 16.9%; Taladorlagia circumcincta, 4.6%; Dictyocaulus spp, 10.7%; Cysticercus tanuicollia, 30.7%; Monlezia axpanza 7.6%; M. banadani, 1.5%; M. denticulata, 1.5%; Thysanoloma actinoidas, 3%; Echinococcus granuloaus, 3%. The most important species for Heap production was Haemonchus, being mora prevalent from mid-January to mid-May. Grater Laval wara seen during sarly autumn.